Multilevel Inverter fed Direct Torque and Flux Control‐Space Vector Modulation of Speed Sensorless Permanent Magnet Synchronous Motor drive with Improved Steady State and Dynamic Characteristics. (15th December 2021) - Pothuraju, Ramakrishna; Tejavathu, Ramesh; Panda, Anup Kumar
Abstract: In this paper, multilevel inverter (MLI) fed direct torque and flux control with space vector modulation (DTFC‐SVM) of speed sensorless permanent‐magnet synchronous motor (PMSM) drive is proposed to improve the steady‐state and dynamic performance characteristics with less torque and flux ripples. In the DTFC‐SVM technique, the speed of PMSM drive is regulated by controlling stator flux and electromagnetic torque directly and independently. The MLIs further extend the performance characteristics of motor drive with reduced electromagnetic torque ripple and improved dynamics. Further, the robustness and reliability of drive system is improved by implementing the speed estimation control technique to eliminate the speed sensor usage. The model reference adaptive system (MRAS)‐based speed estimator is used to estimate the PMSM speed. The proposed method is simulated in MATLAB/SIMULINK environment using two‐level, three‐level, and five‐level inverter under different operating conditions, respectively. The proposed method with five‐level inverter gives very less ripples in electromagnetic torque and stator flux which consequences excellent steady‐state and dynamic performance of drive. The effectiveness and feasibility of the proposed method is validated by implementing hardware prototype and comparing simulation results with the experimental results. Abstract : In this paper, multilevel inverter fed DTFC‐SVM of speed sensorless PMSM drive is proposed to improve the steady‐state and dynamic performance characteristics with less torque and flux ripples. The effectiveness and feasibility of the proposed method is validated by implementing hardware prototype and comparing simulation results with the experimental results.